Modular robots. - Yim, M.
Modular reconfigurable robots-experimental systems made by interconnecting multiple, simple, similar units-can perform shape shifting. A robot made up of a chain of simple hinge joints could shape itself into a loop and move by rolling like a self-propelled tank tread; then break open the loop to form a serpentine configuration and slither under or over obstacles; and then rearrange its modules to "morph" into a multilegged spider, able to stride over rocks and bumpy terrain. This robot, dubbed PolyBot, is being built and experimented with at Xerox Palo Alto Research Center (PARC), in California. This paper describes the main features of PolyBot and how it works. Programming of PolyBot is also discussed
Keywords: PolyBot; Xerox Palo Alto Research Center; Bumpy terrain; Hinge joints; Modular reconfigurable robots; Multilegged spider; Multiple units interconnection; Programming; Rocks; Self-propelled tank tread; Serpentine configuration